1992
DOI: 10.1007/bf03008314
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative clonidine enhances postoperative morphine patient-controlled analgesia

Abstract: In this prospective study, the postoperative analgesic effects of intraoperative iv clonidine were evaluated. Two hundred consecutive patients undergoing major abdominal surgery were randomly assigned to either balanced anaesthesia with iv clonidine (Group 1) 55,4 +--30,6 mg versus 67,1 +_ 45,1 mg dans le groupe 2 (P < 0,05); cette diffgrence est plus marquee dans les 12 premiOres heures aprks la chirurgie (19,7 --+ 11,1 mg versus 27,6 +--18,1 mg;P < 0,001 Adequate postoperative analgesia has become a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…One explanation for prolonged postoperative analgesia with dexmedetomidine may be the anxiolytic and thymoanaleptic properties of α 2 -agonists, which act on the emotional component of postoperative pain. 24 In summary, our results indicate that intraoperatively administered dexmedetomidine has specific analgesic properties and provides effective visceral pain relief. We found that continuous infusion of dexmedetomidine during abdominal surgery significantly reduces the amount of PCA morphine that patients require to remain comfortable postoperatively, without affecting time to extubation.…”
Section: Discussionmentioning
confidence: 65%
“…One explanation for prolonged postoperative analgesia with dexmedetomidine may be the anxiolytic and thymoanaleptic properties of α 2 -agonists, which act on the emotional component of postoperative pain. 24 In summary, our results indicate that intraoperatively administered dexmedetomidine has specific analgesic properties and provides effective visceral pain relief. We found that continuous infusion of dexmedetomidine during abdominal surgery significantly reduces the amount of PCA morphine that patients require to remain comfortable postoperatively, without affecting time to extubation.…”
Section: Discussionmentioning
confidence: 65%
“…1-3, which are individual Forest plots). 18,20,21,24,26,29,33,37,38,43 At 2 h after surgery, the median of all average cumulative morphine equivalents in control subjects was 12.2 mg (range, 7.0 -17.3); clonidine did not significantly decrease this amount. 33,37 At 12 h, the median of the average cumulative morphine-equivalents in controls was 30.1 mg (range, 10.8 -36.0), and clonidine showed a significant morphine-sparing effect (WMD Ϫ9.8 mg).…”
Section: Postoperative Consumption Of Morphine Equivalentsmentioning
confidence: 99%
“…33,37 At 12 h, the median of the average cumulative morphine-equivalents in controls was 30.1 mg (range, 10.8 -36.0), and clonidine showed a significant morphine-sparing effect (WMD Ϫ9.8 mg). 18,20,24,26 At 24 h, the median of the average cumulative morphine equivalents in controls was 16.7 mg (range, 11.0 -49.9), and clonidine significantly decreased this amount (WMD Ϫ4.1 mg). 21,29,38,43 Data on cumulative consumption of morphine equivalents could be combined from eight trials that tested dexmedetomidine ( fig.…”
Section: Postoperative Consumption Of Morphine Equivalentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuncts to opioid therapy include nonsteroidal anti-inflammatory drugs (e.g., ibuprofen) [55], acetaminophen [56], antiarrhythmics, anticonvulsants [57], antidepressants (such as desipramine) [58], antipsychotics, baclofen, benzodiazepines, capsaicin, calcium channel blockers, clonidine hydrochloride [59], central nervous system stimulants, corticosteroids, local anesthetics, N-methyl-D-aspartate receptor antagonists and scopolamine [60,61]. Of these, some (e.g., acetaminophen) are currently routinely used, whereas others (e.g., nifedipine [calcium channel blocker]) are only administered on a limited basis.…”
Section: Strategies To Manage the Adverse Effects Of Morphinementioning
confidence: 99%